Penyuluhan Strategi Keuangan Badan Usaha Milik Desa (Bumdes) dari Konsep Dasar Hingga Implementasi di Desa Sopuraa - A. Musyarrafah Vetriyani; Anshar; Andi Zulkarnain; Abd Haris; Hilda Novitasari; Zulkifli (Santri : Journal of Student Engagement, 2026)
The development of rural economies requires strengthening the governance of Village-Owned Enterprises (BUMDes) to be accountable, transparent, and sustainable. Desa Sopuraa has established a BUMDes to manage local potential in the agricultural sector and opportunities related to nickel mining. However, the management capacity of the administrators in financial management is still limited, resulting in suboptimal business performance. This Community Service Program aims to enhance the capacity of BUMDes Sopuraa's administrators through a series of outreach, practical workshops, case study discussions, and technical assistance over six months. The program's materials cover basic financial management concepts and strategies, the preparation of annual budgets (RAB), cash bookkeeping, simple financial reporting, and the application of principles of accountability and transparency. The main outputs include a BUMDes financial strategy module, planning and reporting documents (annual RAB, bookkeeping formats, and quarterly/annual report templates), and a report on the activities carried out. The targeted impact includes improving financial literacy among administrators, implementing a simple but effective record-keeping system (both manual and digital), changing management practices towards data-driven decision-making, and increasing public trust through standardized reporting practices. This program is expected to serve as a model for structured support to strengthen other BUMDes with similar characteristics.